Americans in the Treasure House : Travel to Porfirian Mexico and the Cultural Politics of Empire - Ruiz, Jason (University of Texas Press, 2014)
"This book examines travel to Mexico during the Porfiriato (the long dictatorship of Porfirio Diaz 1876-1911), focusing especially on the role of travelers in shaping ideas of Mexico as a logical place for Americans to extend their economic and cultural influence in the hemisphere. Overland travel between the United States and Mexico became instantly faster, smoother, and cheaper when workers connected the two countries' rail lines in 1884, creating intense curiosity in the United States about Mexico, its people, and its opportunities for business and pleasure. As a result, so many Americans began to travel south of the border during the Porfiriato that observers from both sides of the border began to quip that the visiting hordes of tourists and business speculators constituted a "foreign invasion," a phrase laced with irony given that it appeared at the height of public debate in the United States about the nation's imperial future. These travelers created a rich and varied record of their journeys, constructing Mexico as a nation at the cusp of modernity but requiring foreign intervention to reach its full potential"--